Results from the Strong Families Start at Home/Familias Fuertes Comienzan en Casa: feasibility randomised control trial to improve the diet quality of low-income, predominantly Hispanic/Latinx children. Issue 4 (24th April 2023) - Tovar, Alison; Fox, Katelyn; Gans, Kim M; Markham Risica, Patricia; Papandonatos, George D; Ramirez, Andrea; Gorin, Amy A; von Ash, Tayla; Jennings, Ernestine; Bouchard, Kelly; McCurdy, Karen
Abstract: Objective: To describe the feasibility, acceptability and results of Strong Families Start at Home, a 6-month pilot trial of a home-based food parenting/nutrition intervention. Design: Pilot randomised controlled trial. Setting: Participants received six visits with a community health worker trained in motivational interviewing (three home visits, three phone calls); an in-home cooking or reading activity; personalised feedback on a recorded family meal or reading activity; text messages and tailored printed materials. Participants: Parents and their 2–5-year-old child were randomised into intervention (responsive food parenting practices/nutrition) or control (reading readiness) groups. Results: Parents ( n 63) were mostly mothers (90 %), Hispanic/Latinx (87 %), born outside the USA (62 %), with household incomes <25 k (54 %). Despite delivery during COVID-19, 63 % of dyads were retained at 6 months. The intervention was delivered with high fidelity. All parents in the intervention group ( n 24) expressed high levels of satisfaction with the intervention, which produced positive treatment effects for whole and total fruit component Healthy Eating Index-2015 scores (point estimate (PE) = 2·14, 95 % CI (0·17, 1·48); PE = 1·71, 95 % CI (0·16, 1·47), respectively) and negative treatment effects for sodium (PE = -2·09, 95 % CI (−1·35, −0·04)). Positive treatment effects also resulted for the following food parenting practices: regular timing of meals and snacks (PE = 1·08, 95 % CI (0·61, 2·00)), reducing distractions during mealtimes (PE = -0·79, 95 % CI (−1·52, −0·19)), using food as a reward (PE = -0·54, 95 % CI (−1·35, −0·04)) and providing a supportive meal environment (PE = 0·73, 95 % CI (0·18, 1·51)). Conclusion: Given the continued disparities in diet quality among low-income and diverse families, continued efforts to improve child diet quality in fully powered intervention trials are needed.